Penurunan Tingkat Kecelakaan Lalu Lintas menuju Zero Accident Melalui Metode Keselamatan Jalan di Ruas Trans Sulawesi Rute Kolaka-Kolaka Utara - Arya Dirgantara; La Ode Dzakir; Al Tafakur La Ode; Sahrul Poalahi Salu; Septi Adnan; Faisal (Jurnal Infrastruktur, 2025)
One of the Trans-Sulawesi road sections that frequently happen traffic accidents is the Kolaka – North Kolaka road section. The protected forest area on the Tamborasi Incline (KM 78 – KM 81) in Iwomenda District, Kolaka Regency is the highest accident-prone area with a total of 87 accidents since 2022. The causal factors are poor road conditions, damaged road equipment, lack of lighting, and driver negligence. The solution to address this problem is by conducting a comprehensive audit on the Kolaka – North Kolaka road section. The purpose of this study is to provide academic studies for the local government in implementing the management of traffic accident-prone areas through road safety audits to reduce the accident rate towards Zero Accident. The method used is the road safety audit method including field surveys, identification of accident-prone points (black spots), road geometric analysis, and evaluation of supporting safety facilities such as signs, markings, and street lighting. The audit results showed that several road segments have significant deficiencies in geometric aspects and the completeness of safety facilities, which directly contribute to the high risk of accidents. The percentage of factors causing accidents are human factors (56.42%), vehicle factors (10%), physical environmental conditions (21.42%), and road conditions (12.14%). Recommendations for improvement are provided based on the audit findings for implementation by relevant parties, such as improving infrastructure quality, adding warning signs, and regulating vehicles. It is hoped that the results of this study can inform policymaking in planning and improving the road transportation system to create a safe and comfortable traffic environment without accidents, aiming for a Zero Accident target in the Kolaka-North Kolaka area.